Bioactive compounds in extracts from short rotation willow shoots known as pharmaceuticals and experimental demonstration of biostimulation of maize plants by these chemical complexes - Zombori, Zoltán; Szalai, Gabriella; Hamow, Kamirán Áron; Hóvári, Miklós; Sass, László; Ferenc, Györgyi; Janda, Tibor; Dudits, Dénes (Frontiers in Plant Science, 2025)
Extracts from willow bark or leaves were shown to contain effective plant biostimulants and pharmaceutical compounds. Considering the limitation in the use of bark raw materials on large scale, here we analyzed the stimulatory effects of extracts from various organs of willow (Salix viminalis L) plants grown as short rotation shrub willow. Metabolomic analysis of water extracts from different organs (leaves, meristems, stems) of two triploid genotypes (Rába and Maros) revealed presence of bioactive compounds. Quantity of phenylpropanoids, flavones, flavonols, anthocyanins, aminobenzoate degradants, plant hormones and stylbenes varied between organs and genotypes. Several of these bioactive compounds are known as pharmaceuticals. Here we carried out phytostimulatory tests by using various extracts for seed priming and foliar spraying of maize plants in greenhouse and field experiments. Both the digital imagining of maize plants and measurements of the plant height showed variable stimulation of growth. Chlorophyll fluorescence parameters indicated improved photosynthetic performance. Increased seed weight/ear and 1000 seed weight (17%) were detected after foliar spraying. The present study supports the extended application of bioactive phytocompounds by offering a novel raw material, the short rotation willow shoots as sources of bioactive compounds for use in agricultural practice and pharmaceutical industry.